Impactos causados às populações do Bairro da Serra, Iporanga e Apiaí devido ao fechamento das cavernas turísticas do PETAR (2008) na visão dos stakeholders - Borsanelli, Francesca Antoniella (Universidade Federal de São Carlos, 2018)
Since the 1960s, the Upper Ribeira State Tourist Park - PETAR - receives visitation in its caves. However, the combination of factors, such as the delicate environment, fragile management and vulnerable security culminated in a civil action, which embargoed the visitation in the tourist caves of the Park, between February and April 2008. After these 2 months, it was resumed. In this scenario, the present work presents the results of a research on the closure of the tourist caves of PETAR, based on the analysis of the content of the stakeholders' opinions. Its main objective was to identify the positive and negative impacts caused to surrounding communities brought by the closure. It also investigates changes in tourist flow and visitor profile, as well as possible improvements in the park's public use, after 2008.The results show that the most relevant positive impacts were greater public use planning, more safety for the visitor and more effectiveness in environmental conservation. The most comprehensive negative impacts were the financial losses, which affected, mainly, the community of the bairro da Serra; and also the emergence of a market reserve, which monopolizes local tourism development, concentrating the gains on the hand of few people. The tourist flow has grown considerably since 2015 and there have been changes in the visitor profile. It was concluded that there are two streams of views on the organization of public use in PETAR after 2008. Some of the stakeholders argued that is more organized and on the other hand, others argue that it is less organized. This relates more to the season when the tour was held, low season or extended holidays. The surrounding community apparently overcame the caves ban and came back to believing in tourism. The best alternative to the surrounding community is currently investing in new attractions outside the park, in order to vent the tourism in the long holidays also decoupling tourism in the region, especially the Park. In addition, it is concluded that the implementation of Speleological Management Plans may be among the measures that would avoid or mitigate much of the negative impacts felt since 2008.
Impacts caused to the populations of Bairro da Serra, Iporanga and Apiaí due to the closure of the tourist caves of PETAR (2008) in the stakeholders' view
Keywords: Espeleoturismo; Impactos do turismo; Planos de manejo espeleológico; Speleotourism; Impacts of Tourism; Speleological Management Plans; Ecoturismo; Ecotourism; CIENCIAS SOCIAIS APLICADAS::TURISMO